INTELLECTUAL CAPITAL: AN INTANGIBLE ASSET - López de Castro, Sandra (Revista Arbitrada Formación Gerencial, 2024)
Intellectual Capital can be defined from various perspectives, but in general most authors agree on defining it as an intangible asset that, despite not being able to be reflected in the accounting accounts of the company or organization, generates added value to the company. same, which can be used in the future and differentiate it from the others, and can even increase its value in the market.